Prospective Multicentric Follow-up Study of Cochlear Implantation in Adults With Single-Sided Deafness: Tinnitus and Audiological Outcomes. Issue 4 (April 2020) - Poncet-Wallet, Christine; Mamelle, Elisabeth; Godey, Benoit; Truy, Eric; Guevara, Nicolas; Ardoint, Marine; Gnansia, Dan; Hoen, Michel; Saaï, Sonia; Mosnier, Isabelle; Lescanne, Emmanuel; Bakhos, David; et al.
Abstract : Objective: This study investigated the audiological and tinnitus outcomes of cochlear implantation (CI) in adults with single-sided deafness (SSD) and tinnitus. Study Design: Multicentered prospective, non-randomized intervention study. Setting: Six French CI centers. Patients: Twenty-six patients with SSD and incapacitating tinnitus (Tinnitus Handicap Inventory [THI] >58) underwent cochlear implantation. Interventions: First, CIs delivered only masking white noise stimulation for 1 month and then standard CI stimulation. Main Outcome Measures: Before and after CI surgery, patients completed the THI, Tinnitus Reaction Questionnaire (TRQ), Subjective Tinnitus Severity Scale (STSS), and two visual analogue scales quantifying tinnitus loudness and annoyance. Speech perception in spatialized noise was tested at 13 months. Results: The first month of white noise stimulation triggered a significant improvement in THI scores (72 ± 9 to 55 ± 20, p  < 0.05). No change was observed for the other measures. After 1 year of standard CI stimulation, 23 patients (92%) reported a significant improvement in tinnitus. This improvement started 1 to 2 months after CI and exceeded 40% improvement for 14 patients (54%). Average speech-in-noise perception after 1 year significantly improved for the 23 patients who completed these measures. Conclusions: CI is efficacious to reduce the handicap of patient with SSD and incapacitating tinnitus, leading to a decrease in reported tinnitus and partial restoration of binaural hearing abilities.